Does grit reduce job-hopping intentions? Evidence from millennial industrial workers in Purwakarta, Indonesia - Sutisna, Deden; Hayati, Neuneung Ratna; Marinda, Vina Silviani (Program Magister Ilmu Ekonomi Pascasarjana Universitas Jambi, 2025)
This study examines the relationship between grit and job-hopping intention among millennial employees in the industrial sector of Purwakarta Regency, West Java, Indonesia. Millennials are often considered a challenging generation to manage due to their dynamic work behavior and tendency to change jobs frequently. Using a quantitative approach, data were collected through 100 questionnaires from industrial workers and analyzed using validity, reliability, regression, correlation, and determination tests. The results revealed that grit among respondents was relatively low, while job-hopping intention was relatively high. Regression analysis confirmed that grit had a significant negative effect on job-hopping intention, indicating that employees with higher perseverance and resilience were less likely to intend to leave their jobs. The coefficient of determination indicated that grit explained 22.6% of the variation in job-hopping intention, with the remainder influenced by other factors, such as compensation, career opportunities, and work–life balance. These findings suggest that organizational strategies to strengthen grit, combined with supportive labor market policies, are crucial for reducing turnover intentions and enhancing workforce stability in the industrial sector.